2000
DOI: 10.1016/s0038-1098(00)00204-0
|View full text |Cite
|
Sign up to set email alerts
|

The spectral, structural and transport properties of the pseudogap system (TaSe 4 ) 2 I

Abstract: Abstract.The room temperature "metallic" properties of the quasi-one-dimensional material (TaSe 4 ) 2 I differ markedly from those expected of either a Fermi or a Luttinger Liquid, showing strong signs of a suppression of the density of states at the Fermi level. We present evidence for the existence of strong quasi-static fluctuations of structural order with long correlation length. These fluctuations produce a pseudogap in the density of states. We compute the temperature dependence of the optical and DC co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…This enables us to find an extrapolation of σ 1 (ω) in the frequency regime 0 < ω 0.1. We would like to note that our results differ from perturbative results of the optical conductivity which were calculated within the same model to first order in perturbation theory without considering vertex corrections [12]. The perturbative results give a finite dc conductivity which for this model must be an artifact of perturbation theory but nevertheless explain the qualitative behavior of the dc conductivity of Peierls systems above their charge density wave transition.…”
contrasting
confidence: 68%
“…This enables us to find an extrapolation of σ 1 (ω) in the frequency regime 0 < ω 0.1. We would like to note that our results differ from perturbative results of the optical conductivity which were calculated within the same model to first order in perturbation theory without considering vertex corrections [12]. The perturbative results give a finite dc conductivity which for this model must be an artifact of perturbation theory but nevertheless explain the qualitative behavior of the dc conductivity of Peierls systems above their charge density wave transition.…”
contrasting
confidence: 68%
“…Ternary compounds belonging to the family Cu 3 -M-VI 4 (M = V, Nb, Ta, VI = S, Se, Te) are interesting materials due principally to their potential applications as electronic devices, especially as light-modulators [1,2]. Earlier studies on the lattice vibration in the sulfide and selenide compounds revealed that they belong to the p-type semiconductors [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Ternary compounds belonging to the family Cu 3 MSe 4 (M = V, Nb, Ta) are interesting materials due principally to their potential applications as electronic devices, especially as lightmodulators [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%